Local asymptotic normality of statistical models of discrete martingales - Kanišauskas, Vaidotas (Lietuvos matematikos rinkinys, 2023)
We establish general conditions assuring the local asymptotic normality of statistical experiments of discrete or purely discontinuous local martingales obtained models of point processes of all types were found out. The general conditions include the Fréchet differentiability of parameters in probability in normed spaces with regard to a continuous compensator.